Towards regularisation: Morphological spelling in several editions of the Kalender of Shepherdes - Rutkowska, Hanna (My University, 2013)
This corpus-based study focuses on the graphemic realisations of several derivational suffixes in thirteen editions of the Kalender of Shepherdes, an early modern almanac published between 1506 and 1656. Morphological spelling, that is, the consistent representation of particular morphemes, is considered to be one of the most important criteria in research on the orthographic standardisation in English. The analysis of the graphomorphemic information available in the documents under consideration indicates that particular printing houses applied different combinations of spelling rules with regard to the variants of suffixes and were characterised by varying levels of consistency in the use of these graphemic representations. The new spelling variants of the suffixes were adopted partly as the printers’ own regularisation policy, and partly under the influence of normative writings.
Keywords: standardisation; standaryzacja; spelling; pisownia; early printed books; pierwsze książki drukowane; morphology; morfologia; suffixes; przyrostki